Gender Gaps in Equity Crowdfunding: Evidence from a Randomized Field Experiment - Bapna, Sofia; Ganco, Martin (Management Science, 2021)
Although prior research in traditional equity financing shows that male founders are preferred, emerging evidence in low-stakes crowdfunding (e.g., rewards-based crowdfunding) indicates that female entrepreneurs may have an advantage, particularly with female investors. We seek to examine whether investors in high-stakes equity crowdfunding, which includes elements from both traditional equity financing and low-stakes crowdfunding, respond differently to male and female founders. Specifically, we examine whether founder gender preferences, if they exist, vary based on the gender and the experience of the investor. Through a randomized field experiment, we find that inexperienced female investors are significantly more interested (138%) in ventures with female founders than those with male founders; however, we do not observe founder gender preferences among experienced female investors. For male investors, we do not observe differences in interest based on founder gender or investor experience. Thus, we confirm that the gender gaps observed in traditional equity financing are ameliorated in the equity crowdfunding context. Furthermore, we identify a boundary condition to the preference for female founders reported in earlier work involving low-stakes crowdfunding. In high-stakes crowdfunding, investor experience serves as a contingency that reduces female investors’ preference for female founders, potentially because of the weakening effects of activism homophily and the lower reliance on heuristics as investor experience increases. This paper was accepted by Sridhar Tayur, entrepreneurship and innovation.